Implementation of a centralized discharge planning office during the COVID-19 pandemic: translating the experience from the emergency to routine clinical practice - Pregliasco, Fabrizio; Caimi, Barbara; Falco, Roberto; Valentini, Giuseppa; Capello, Federico; Pellegrini, Matteo; Valtorta, Miranda; Curci, Elisabetta; Bertozzi, Federica; Calicchio, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Background and aim During the COVID-19 emergency, the lombardy region (northern Italy) implemented a regional Centralized Discharge Planning Office (CDPO) to promptly manage the discharge requests, rapidly match the needs of discharge hospitals with the availability of admission facilities and ensure the management of the entire discharge process. To improve the discharge process in routine clinical practice, maintaining the role of the CDPO could be of great interest. This paper describes the experience of the CDPO during the COVID-19 pandemic and discusses the possibility to translate this operational model to routine clinical practice. Methods: The PRIAMO web portal was developed to manage discharge requests with centralized and standardized procedures. The activity on PRIAMO consisted of three stages: discharge request, sorting process, and discharge follow-up phase. To evaluate the activity of the CDPO, these indicators were considered: average time (hours) between patient discharge and transfer acceptance; average time (hours) between patient discharge and effective admission to the new facility; percentage of transfers whose destination was found directly by the CDPO; percentage of reallocations beyond 24 hours; mean distance between discharge and admission facilities. Results: Process indicator evaluation showed a great reduction in the time between the discharge and the admission to post-acute care facilities. Transfers whose destination was found directly by the CDPO progressively increased. Reallocations beyond 24 hours by the CDPO decreased, suggesting an improvement in the quality of the operations. Conclusions: Centralized discharge planning has enabled timely and efficient management of discharge requests even in the moment of a surge, saving time and costs for acute care hospitals.